Indomethacin Therapy in Premature Infants with Patent Ductus Arteriosus - Cholid Rasidi; Bambang Madiyono; Ismeet N. Usman (Indonesian Pediatric Society, 1982)
Indomethacin has been shown to be effectil'e in closing patent ductus arteriosus (PDA) in premature infants. Indomethacin admin.istration decreased the need for assisted ventilation and surgical closure of PDA. Six premature neonates with birth weight less than 2500 gm diagnosed clinically as PDA were given indomethacin. The drug was given as a single dose by mouth or nasogaYtric tube in 2 or 3 consecutlve days. The dose in the first two days was 0.1 mg/kg BW and the last dose (If necessary) was- 0.3 mg/kg BW. Closure of PDA was observed in all six cases. This experience in the use of indomethacin in PDA indicates a need for a further study of the effect of indomethacin in PDA.